Earthly Love from Avicenna' View - mahmood seidy; mohammadjavad pashaei (حکمت سینوی, 2022)
Earthly love is one of the psychic qualities that human beings experience in their lives. A descriptive analytical study of Avicenna' views shows that earthly or erotic love is basically a kind of mental illness that sometimes leads to physical illnesses. This kind of love is the result of the domination of mental thoughts and imaginations over human beings.  The beloved of earthly love may be any material object, including inanimate objects, plants, animals, and human beings; of course the most important example of such interest is the love of human to another human being. Avicenna's strategies for treating the disease of earthly love are: receiving the lover to the beloved, attracting the lover to the attention of another beloved, and strengthening the physical and material powers of the lover. In contemporary psychology, lustful love can be synchronized with the Avicenna's view about earthly love.